A comparison of osteobiol gen_oss with normal healing extraction socket in quality and quantity of bone formation for implant placement in partial edentulous patients - Mojgan Paknejad; Yadollah Soleimani Shayesteh; Zahra Nasr Esfahani; Nina Rezomeh; Mohadeseh Heidari; Ali Mehrfard (Tehran University of Medical Sciences, 2014)
Background and Aims: The increase in the number of complex implant cases has drawn the attention of researchers toward materials having bone regeneration promoting ability. Socket preservation and bone graft are recommended to minimize bone resorption. The aim of this study was to evaluate a kind of xenograft collagenic bone (osteo biol gen_oss) in socket regeneration.   Materials and Methods: This randomized clinical trial was performed in 12 cases (6 in test and 6 in control groups) with two hopeless teeth. After tooth extraction, in test group, graft material was put in sockets but in the control group the socket was healed naturally. Three months later, during implant placement the specimens from both sites were sent to a pathologist for histologic and histomorphometric evaluations. Data were analyzed using Mc Nemar and Wilcoxan sigh rank test (α=0.05).   Results: There were no significant differences between two groups in foreign body reaction, inflammation, bone vitality and percentage of bone gain. Average percentage of residual graft in test site was 6.73±1.43.   Conclusion: Osteobiol gen_oss xenograft is an appropriate biocompatible osteoconductive material that promotes bone regeneration at 3 months following socket preservation in human extraction sockets.